The impact of entrepreneurship education, role model, and university support on the entrepreneurial mindset among university students - Muhammad Uzair Ismail; Aisyatul Amaniyah Musa; Nur Hawa Ainafatini Mohd Fadzil; Roslina Alimuddin (2024)
The graduate unemployment rate is one of the current issues being discussed by Higher Education Institutions. Every year, there are more than 250,000 students graduate, but one in five fresh graduates remain unemployed 6 months after graduation. Among these fresh graduates with tertiary education, about 26% first-degree holders are unemployed. Due to that, the Ministry of Higher Education (MOHE) urges all higher learning institutions to develop entrepreneurial mindset through entrepreneurship education in the institutions. The purpose of this study is to determine the contribution of entrepreneurship education, role model, and university support, towards entrepreneurial mindset among university students. The data was collected from the final-year undergraduate students in Malaysia. This study used a purposive sampling technique to select a specific group of individuals or units for analysis. The results shows that entrepreneurship education, university support and role model have a significant relationship with entrepreneurial mindset. Furthermore, the findings indicated that entrepreneurship education and university support have contributed positively towards the entrepreneurial mindset among university students with entrepreneurship education as the highest contributor. Consequently, this study managed to discover several implications which are, high level of entrepreneurship knowledge shows that entrepreneurship is well-received while also becoming one of the achievable career choices, and with continuous support from university management will help create an entrepreneurial culture in universities. Therefore, the significant relationship of entrepreneurship education, role models, and university support on entrepreneurial mindset indicates that further development and advancement of the curricular model involving university students are essential to have more successful entrepreneurs.